Análise da influência das variáveis de produção do biochar para adsorção de nutrientes - Gonçalves, Karoline Yoshiko (2021)
In agricultural activity, it is common to use fertilizers to correct qualified soil, greater productivity, however, its low efficiency and a high level of loss, due to non-absorption by plants, can cause financial losses and environmental resources. In this sense, biochar with the addition of nutrients, has stood out as an excellent fertilizer since it has numerous benefits to the soil and plants. However, how to achieve high porosity, a necessary characteristic of biochar for nutrient adsorption, is still a matter of debate. In this context, the present research aims to assess the contribution of biochar production variables that assist in the adsorption of nutrients. After identifying the most important variables (biomass and temperature of production), it was possible to produce the biochar from Citriodora and Grandis eucalyptus, at 350 and 500 ºC, with and without chemical modification. The porosity was quantified and organized (micro, meso and macropores) with the aid of Scanning Electron Microscopy (SEM) and digital image processing using the ImageJ software. The results were caused graphically and statistically. The resulting coal sample from Citriodora eucalyptus, pyrolyzed at 350 ºC without chemical modification, presented statistically obtained results, since the micropores are influenced by the temperature and the mesopores by the biomass taking advantage of the production process. Graphical analyzes, on the other hand, are the ones that present the best behavior and are produced from Citriodora eucalyptus, pyrolysates at 500 ºC, and, as modified with the 1.5% FeCl3 modification, another larger total pore area and, without chemical modification, more pores.